The Messiah Comes to Middle-earth : images of Christ's threefold office in the Lord of the Rings - Ryken, Philip Graham, 1966-; Richter, Sandra L.; McNutt, Jennifer Powell; Struthers, William M., 1970-; Hansen, G. Walter, 1946-; Wheaton College (Ill.). Marion E. Wade Center (Downer's Grove, Illinois : IVP Academic, 2017)
Based on the inaugural Hansen Lectureship series delivered by Philip Ryken at the Marion E. Wade Center, this volume mines the riches of Tolkien's theological imagination. In the characters of Gandalf, Frodo, and Aragorn, Ryken hears echoes of the threefold office of Christ--his prophetic, priestly, and royal roles. Guided by Ryken, readers will discover that they can learn much about the one who is the true prophet, priest, and king through Tolkien's imaginative storytelling.
The Prophetic Ministry of Gandalf the Grey -- Response: Sandra Richter -- Frodo, Sam, and the Priesthood of All Believers -- Response: Jennifer Powell McNutt -- The Coronation of Aragorn Son of Arathorn -- Response: William Struthers.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- In literature; Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation; Tolkien, J. R. R. -- 1892-1973 -- Characters; Christianity in literature